Now you see it, now you don't: representational pseudoneglect during computer maze navigation. - Bartlett, Megan L.; Gwinn, O. Scott; Thomas, Nicole A.; Nicholls, Michael E.R. (Laterality, 2026)
Pseudoneglect refers to the tendency for neurologically normal individuals to overattend to the left side of near space, which shifts to the right in far space. Such attentional asymmetries affect daily activities, such as navigation, where individuals have been found to deviate to the right when passing through an aperture. Interestingly, a representational form of pseudoneglect exists for briefly presented stimuli that need to be held in memory, whereby attention is shifted to the left. The current study examined whether representational pseudoneglect exists in a simulated navigation environment. Participants navigated through the centre of a computer-generated doorway or line. On perceptual trials, the doorway/line would remain on screen, while for representational trials, the doorway/line would disappear from the screen. Significant rightward biases were found for both the perceptual and representational trials of the line and doorway conditions, with the biases being exacerbated on representational trials. Results indicate that the significant load involved with holding a representation of the stimulus in memory may best explain the exacerbation of rightward shifts of attention in the present study.